2017
DOI: 10.3390/atmos8120246
|View full text |Cite|
|
Sign up to set email alerts
|

Utilization of Global Precipitation Datasets in Data Limited Regions: A Case Study of Kilombero Valley, Tanzania

Abstract: This study explored the potential for bias correction of global precipitation datasets (GPD) to support streamflow simulation for water resource management in data limited regions. Two catchments, 580 km 2 and 2530 km 2 , in the Kilombero Valley of central Tanzania were considered as case studies to explore three GPD bias correction methods: quantile mapping (QM), daily percentages (DP) and a model based (ModB) bias correction. The GPDs considered included two satellite rainfall products, three reanalysis prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Readers are recommended to refer to Schultz [99] for more details on the opportunities and challenges of the utilization of RS in hydrological modeling. Appropriate technical skills on how to utilize secondary data from RS to calibrate or infer model parameters have enabled various researchers to improve the robustness of their respective hydrological models [88,101,102].…”
Section: Implications For Hydrological Modelingmentioning
confidence: 99%
“…Readers are recommended to refer to Schultz [99] for more details on the opportunities and challenges of the utilization of RS in hydrological modeling. Appropriate technical skills on how to utilize secondary data from RS to calibrate or infer model parameters have enabled various researchers to improve the robustness of their respective hydrological models [88,101,102].…”
Section: Implications For Hydrological Modelingmentioning
confidence: 99%
“…Using standardized precipitation index in the east coast of Tanzania, Hassan et al [5] also found that this region has recently been experiencing more than one drought episode per year. Because TDD shows an average of 2 to 6 months, and the dry period in the Kilombero catchment is usually between June and October [21,[53][54][55], this implies that sometimes drought spells might coincide with dry periods (as shown in Figure 4d).…”
Section: Findings On Drought Characteristicsmentioning
confidence: 99%
“…The authors would like to correct the published article [1], following the detection of editorial mistakes by the main author, as explained below. Table 5 should now be considered as Table 6.…”
mentioning
confidence: 99%